1998
DOI: 10.1034/j.1399-3054.1998.1030102.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate levels among winter wheat cultivars varying in freezing tolerance and snow mold resistance during autumn and winter

Abstract: The LT50 values and soluble carbohydrate levels in wheat (Triticum aestivum L.) crowns and leaves were monitored throughout autumn and winter in cultivars varying in freezing tolerance and snow mold resistance during 1993/1994 and 1994/1995 in the field at Sapporo, Japan. During the first stage of hardening, from sowing to mid‐November, the pattern of accumulation of mono‐ and disaccharides was similar for all cultivars. During the second stage of cold hardening, from mid‐November to mid‐December, the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 0 publications
9
170
0
1
Order By: Relevance
“…In the shoots, the main component was glucose, probably as a result of starch hydrolysis during periods of water restriction and high temperatures. Several studies have demonstrated the role of this sugar in osmotic adjustment under water and heat stresses (Vágújfalvi et al, 1999;Yoshida et al, 1998;Liu and Huang, 2000). In the roots, on the other hand, the most important sugar was sucrose, with higher levels during the dry season for both species, suggesting a storage function, as well as a role in the maintenance of osmotic potential in the underground organs among other functions.…”
Section: Discussionmentioning
confidence: 99%
“…In the shoots, the main component was glucose, probably as a result of starch hydrolysis during periods of water restriction and high temperatures. Several studies have demonstrated the role of this sugar in osmotic adjustment under water and heat stresses (Vágújfalvi et al, 1999;Yoshida et al, 1998;Liu and Huang, 2000). In the roots, on the other hand, the most important sugar was sucrose, with higher levels during the dry season for both species, suggesting a storage function, as well as a role in the maintenance of osmotic potential in the underground organs among other functions.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between freezing tolerance and soluble sugar content has been documented in a number of studies (26)(27)(28)(29). Soluble sugars function as cryoprotectants and osmolytes that protect cells from freezing damage (30).…”
Section: Effects Of Npk1 On Sugar Metabolism In Maizementioning
confidence: 99%
“…Tamura et al (1985) and Tamura (1986) reported that species and cultivars of winter annual and biannual grasses that contain a larger amount of NSCs survive winter at a higher rate and grow better in the next spring. Yukawa and Watanabe ( 1995) and Yoshida (1998) also clarified that tolerance to snow mold and freezing in wheat and barley were correlated to a great extent with total mono -and disaccharide and fructosan in late fall. The concept that reserve carbohydrates stored in the fall physiologically strengthen winter hardiness and promote growth in the following spring is well accepted.…”
Section: Resultsmentioning
confidence: 99%